Solidified reverse micellar solution-based chitosan-coated solid lipid nanoparticles as a new approach to enhance oral delivery of artemether in malaria treatment - Franklin Chimaobi Kenechukwu; Kingsley Chinazam Ugwu; Chibuzor Stanley Offorbuike; Enyi Moses Ojukwu; Thaddeus Harrison Gugu; Reuben Ejike Eze; Chinazom Precious Agbo; Mumuni Audu Momoh; Anthony Ikechukwu Onah; Chinekwu Sherridan Nwagwu; Onyinyechi Lydia Ugorji; Emmanuel Chekwube Ossai; et al. (BMC Chemistry, 2025)
Abstract Solidified reverse micellar technology and surface-modification are promising techniques for improving the biopharmaceutical properties of poorly water-soluble drugs such as artemether, a first-line antimalarial drug. Thus, the aim of this study was to develop and evaluate artemether-loaded chitosan-coated solid lipid nanoparticles (SLNs) based on solidified reverse micellar solution (SRMS) for improved oral malaria therapy. Artemether-loaded and unloaded SLNs were prepared from optimized SRMS (consisting of Phospholipon® 90G and Compritol® ATO 888 at 3:7 ratio) with or without chitosan by high-shear melt-homogenization, and thereafter characterized for physicochemical performance, stability, safety and antimalarial activity using Plasmodium berghei-infected mice. Results showed both smooth and irregular particles with a layer of polymer coating in chitosan-modified SLNs, increased drug amorphization as well as compatibility of the drug and excipients employed in the formulations. The optimized formulation was stable and nanomeric (size 292.90 ± 5.01 nm, polydispersity index 0.191 ± 0.09, and zeta-potential + 32.50 ± 1.58 mV) with good encapsulation efficiency (82.03%), demonstrated minimal toxicity on Caco-2 cells, exhibited controlled drug release compared with fast release of artemether suspension and gave significantly (p < 0.05) greater antimalarial activity than artemether suspension. Artemether-loaded chitosan-coated SRMS-based SLNs improved the antimalarial activity of the drug and can be pursued as a novel alternative for improved oral malaria treatment.